KYRGYZSTAN’S ISLAMIC REFERENCE POINTS: THE ROLE OF FOREIGN RELIGIOUS TRENDS - ESENAMANOVA, Nurgul (CENTRAL ASIA AND THE CAUCASUS, 2015)
This article examines Kyrgyzstan’s Islamic reference points that formed under the influence of the Islamic movements coming from Turkey, Saudi Arabia, Iran, and the states of the Indian Peninsula. It identifies the institutionalization aspects of these Islamic movements and how Kyrgyz society perceives them.